High-Precision Control for Switched Reluctance Motor With Current Information - Tao, Zean; Li, Mengqiu; Xu, Mingyi; Liu, Jianlin; Luo, Jianguo (Frontiers in Energy Research, 2022)
Magnetic characteristics of the SRM can be monitored directly in the detection of commutation instants. However, the mutual inductance effect between the adjacent phases is prominent for the switched reluctance motor when the adjacent phases are energized simultaneously. Consequently, mutual coupling will distort the response current profile of the injection voltage phase, thereby affecting position estimation precision. In order to acquire a precise estimation and accommodate it for the SRM drive system, it is necessary to take into consideration the modifications for the sensor-less scheme. This study presents a unique rotor position estimation approach to eliminate the mutual inductance effect by using the phase current slope difference method. The sensor-less scheme is achieved by setting a low and a high threshold, and a series of voltage pulses are injected in the idle phase alternately, synchronizing with the chopping current control. Without prior knowledge of mutual inductance and any additional position sensor, a precisely estimated rotor position is achieved. A dynamic model of a 12/8 SRM model is established to evaluate its validity, and both simulation results and experimental evaluation indicate that the proposed sensor-less control can be accomplished with an adequate precision used in a variety of applications.